Anti‐tumour effects of a macrolide analog F806 in oesophageal squamous cell carcinoma cells by targeting and promoting GLUT1 autolysosomal degradation. (13th June 2022) - Li, Xiang; Li, Liyan; Wu, Xiaodong; Wen, Bing; Lin, Wan; Cao, Yufei; Xie, Lei; Zhang, Hefeng; Dong, Geng; Li, Enmin; Xu, Liyan; Cheng, Yinwei
Abstract : Cancer cells are characterized by altered energetic metabolism with increasing glucose uptake. F806, a 16‐membered macrodiolide analogue, has anti‐tumour effects on oesophageal squamous cell carcinoma (ESCC) cells. However, its precise anti‐tumour mechanism remains unclear. Here, metascape analysis of our previous quantitative proteomics data showed that F806 induced glucose starvation response and inhibited energy production in ESCC cells. The reduced glucose uptake and ATP production were further validated by the fluorescent methods, using glucose‐conjugated bioprobe Glu‐1‐O‐DCSN, and the bioluminescent methods, respectively. Consistently, under F806 treatment the AMP‐activated protein kinase signalling was activated, and autophagy flux was promoted and more autophagosomes were formed. Moreover, live‐cell imaging and immunofluorescence analysis showed that F806 induced GLUT1 plasma membrane dissociation and promoted its internalization and autolysosome accumulation and lysosome degradation. Furthermore, molecular docking studies demonstrated that F806 bound to GLUT1 with a comparable binding energy to that of GLUT1's direct interacting inhibitor cytochalasin B. Amino acid mutation was used to test which residues of GLUT1 may participate in F806 mediated‐GLUT1 internalization and degradation, and results showed that Thr137, Asn411 and Trp388 were required for GLUT1 internalization and degradation, respectively. Taken together, these findings shed light on a novel anti‐tumour mechanism of F806 by targeting and promoting GLUT1 internalization and further autolysosomal degradation. Abstract : F806, a 16‐membered macrodiolide analogue, interacted with GLUT1 by residues Thr137, Asn411 and Trp388, which inhibited glucose binding to GLUT1 and leads to glucose deprivation and autophagy initiation. Meanwhile, the plasma membrane‐localized F806‐GLUT1 complex was promoted to internalize to autophagosome and finally degraded in lysosome. Our study proposed a novel anti‐tumour mechanism of F806 by targeting and promoting GLUT1 internalization and further autolysosomal degradation.